Kebijakan Trans Pakuan Bogor - Utami, Hanna; Arianto; Sulistiawan, Dani Putra; Rohmah, Tri Ainun; Yakin, Muhammad Ainul; Kurniawan, Irfan Arif (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
One of the transportation options in the city of Bogor is the Trans Pakuan Bus, sometimes referred to as the Ragit Transit Bus. It began operations on June 3, 2007, travels 14 kilometers in roughly 45 minutes, and serves the Baranangsiang Bubulak corridor. This line has 16 stops total. Instead of using dedicated lanes, this city bus operates Type 34 buses. The term